THE INFLUENCE OF CARBON STEEL STRUCTURAL COMPONENTS DISPERSION ON FRACTURE RESISTANCE - Vakulenko, I. O.; Hryshchenko, M. A.; Perkov, O. M. (Science and Transport Progress, 2007)
The observed questions of estimate stress intensity coefficient, strength of fatique and toughness behavior is considered to be result of a directional variation in the grain size of austenite and size of ferrite pearlite in carbon steel.